CUSTARD, CULVERTS AND CAKE : academics on life in the archers. (EMERALD Group PUBL, 2017)
Leading scholars from the Academic Archers network combine a love of The Archers with their specialist subjects, in Custard, Culverts and Cake - a sometimes serious, but most often wry look at the people of Ambridge. Scholars take on subjects such as food, geography, social media, faith and naturally, the Helen and Rob storyline.
Keywords: Archers (Radio program); Ambridge (Imaginary place); elektronické knihy; electronic books